Paracrine control of steroidogenesis by serotonin in adrenocortical neoplasms. (15th June 2015) - Lefebvre, H.; Duparc, C.; Prévost, G.; Zennaro, M.C.; Bertherat, J.; Louiset, E.
Highlights: 5-HT stimulates steroid secretion in the normal human adrenal via 5-HT4 receptors. 5-HT is abnormally produced in adrenocortical hyperplasias and tumors. 5-HT receptors are overexpressed in adrenocortical neoplasms. 5-HT exerts a paracrine stimulatory effect in steroid-producing adrenal neoplasms. Abstract: Serotonin (5-hydroxytryptamine; 5-HT) is able to activate the hypothalamo–pituitary–adrenal axis via multiple actions at different levels. In the human adrenal gland, 5-HT, released by subcapsular mast cells, stimulates corticosteroid production through a paracrine mode of communication which involves 5-HT receptor type 4 (5-HT4 ) primarily located in zona glomerulosa. As a result, 5-HT is much more efficient to stimulate aldosterone secretion than cortisol release in vitro and administration of 5-HT4 receptor agonists to healthy individuals is followed by an increase in plasma aldosterone levels without any change in plasma cortisol concentrations. Interestingly, adrenocortical hyperplasias and tumors responsible for corticosteroid hypersecretion exhibit various cellular and molecular defects which tend to reinforce the intraadrenal serotonergic tone. These pathophysiological mechanisms, which are summarized in the present review, include an increase in adrenal 5-HT production and overexpression of 5-HT receptors in adrenal neoplastic tissues. Altogether, these data support the concept of adrenal serotonergic paracrinopathy and suggest that 5-HT and its receptors may constitute valuable targets for pharmacological treatments of primary adrenal diseases.